Extramedullary left temporal plasmacytoma resembling as meningioma: a case report and literature review - Sharma, Gopal Raman; Deo, Alok; Aryal, Samir; Shrestha, Ram Chandra; Bhattachan, Maya; Joshi, Sumit; Shah, Dambar Bikram; Pathak, Rakesh (Nepal Mediciti Medical Journal, 2025)
When plasmacytoma occurs outside bone marrow, it is called extramedullary plasmacytoma (EMP), a rare malignant disorder due to excessive proliferation of abnormal plasma cells in other system of the body like the gastrointestinal tract, thyroid glands, breast, kidney, and central nervous system (CNS). Extramedullary plasmacytoma involving the central nervous system is very rare and may involve skull, dura mater, brain parenchyma and spines. Hence, we present a very rare care of EMP of left temporal lobe involving bone, dura and brain parenchyma on a 56-year-old righthanded gentleman who presented with left-sided V2 trigeminal neuralgia. In this case report, we will be discussing on natural course, clinical pathological characteristics, diagnosis, treatment, and prognosis of intracranial EMP.